2013
DOI: 10.5505/phd.2013.58088
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Relationship in Between Burnout and Depression in Primary Caregivers of Chronic Mental Problem Patients

Abstract: ÖZETAmaç: Çalışma kronik ruhsal sorunlu hastaların primer bakım vericilerinde tükenmişlik ve depresyon arasındaki ilişkiyi incelenmek amacıyla yapıldı. Bulgular: Bakım vericilerde tükenmişliğin alt gruplarından duygusal tükenme, duyarsızlaşma ve kişisel başarıda düşme ile depresyon puanları arasında anlamlı ilişki olduğu, duygusal tükenme, duyarsızlaşma ve kişisel başarıda düşme arttıkça depresyonun arttığı saptandı. Bakım vericilerin medeni durum, meslek, yaşadığı yere göre tükenmişlik ve depresyon puanı aras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
1
5
1
8
Order By: Relevance
“…In many studies, duration of care was found to be one of the main variables affecting burnout. There are also studies that could not find an association between burnout and duration of care (23,25,32).…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, duration of care was found to be one of the main variables affecting burnout. There are also studies that could not find an association between burnout and duration of care (23,25,32).…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] Literatürde bakımverenin algıladığı yükün, depresyon, anksiyete, tükenmişlik, fiziksel sağlıkta azalma, sosyal destek gibi değişkenlerle ilişkili olduğu belirtilmiştir. [3,7,51] Ancak bakım vermenin, fizyolojik ve psikolojik problemlerin gelişmesine neden olduğu veya bu problemlere yol açtığı ya da bu problemlerin, bakım vermeyi güçleştirdiği ile ilgili net bir şey söylemek mümkün değildir.…”
Section: Discussionunclassified
“…Analytical studies on caregivers have reported that the burden perceived by caregivers is associated with variables such as depression, anxiety, burnout, social support and quality of life (Atagün et al., ; Aydın et al., ; Gülseren et al., ; Nehir Türkmen, ; Schulze & Rössler, ; Tel & Ertekin, ; Toyoshima, Washio, Miyabayashi, Haruna, & Arai, ; Zahid & Ohaeri, ). However, in the literature review, there were no studies examining the relationship between caregiver burden and caregivers’ anger expression styles.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary models pertaining to the provision of mental health services place importance on community‐based treatments and long‐term hospitalisation. Data have shown that 50%–90% of patients with a chronic psychiatric disease start living with their families after receiving acute psychiatric treatment (Ak, Yavuz, Lapsekili, & Türkçapar, ; Schulze & Rössler, ; Tel & Ertekin, ). When a patient with a psychiatric disease requires continuing care in a family, this can cause stress and impair familial functions, and even place various burdens on the shoulders of family members (Addington, ; Gülseren, ; Li, Lambert, & Lambert, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation